Principal Leadership-Based Learning (A Site Study atSenior High School 1 Weleri Kendal) - Dwianto, Dwianto (2012)
The objectives of this research are to describe (1) characteristic of principal leadership based learning in managing personal mastery; (2) characteristic of principal leadership based learning in managing shared vision, (3) characteristic of principal leadership based learning in managing public and team learning. It is a qualitative research using ethnography design. This research was conducted at Senior High School 1 Weleri Kendal. The informants are principal, vice principal, and teachers. Data collection used observation, in-depth interview, and documentation. Data analysis used data reduction, data display, and drawing conclusion. The results of research show that: (1) the principal leadership based learning in managing the personal mastery is realized in creating the conducive culture and determining the school rules and policy. The conducive culture is created by delegating the authority, building effective communication, and involving the school component in taking decision. The principal created rules for school community; (2) The principal leadership in managing shared vision is realized in creating the school vision and mission. The school vision and mission have four aspects, normative, academic, relevant and visionary. Things which are considered in creating the school vision and mission are SWOT analysis about the strength, weakness, opportunity, and threats. The principal can analyze the available source condition at school and find the priority scale and create the school programs relevant to the school vision and mission; (3) Principal leadership is realized in improving the quality or human resource or school personnel such as classifying teacher's task, improving the competence, giving motivation, and supervising or teacher's performance. Teacher and school personnel have a chance to continue their study to the advance level, reward and award and motivation in the form of religious motivation. Activities to develop teacher's professionalism are held regularly and continuously in training, workshop, comparison study and Subject matter Teacher' Forum. The professionalism development activities for school personnel are not held regularly. The improvement activity is also done for students both in academic and non academic activities.